Public Perception of the Benefits of Walking for Weight Loss - Linda Andariyanti; Ruslan Rusmana; Dindin Bern Hardin (STKIP Pasundan Press, 2026)
This study aims to identify public perceptions of the benefits of walking in losing weight, especially in the Cimahi City community. Walking as a form of light physical activity is considered to have great potential in supporting a healthy lifestyle and weight loss. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews with 10 informants with different age and occupational backgrounds. The results of the study indicate that most people are aware of the benefits of walking in maintaining fitness and supporting weight loss, although not all respondents directly use walking as the main method for dieting. The driving factors underlying walking activities are convenience, low cost, and habits in daily activities. Meanwhile, the obstacles that are often faced are weather conditions, laziness, busyness, and negative social perceptions of walking activities. These findings show that walking has a recognized health value, but still requires wider environmental support and education so that people consistently make this activity part of a healthy lifestyle.